Ligand‐Based Control of Single‐Site vs. Multi‐Site Reactivity by a Trichromium Cluster. (27th March 2019) - Bartholomew, Amymarie K.; Juda, Cristin E.; Nessralla, Jonathon N.; Lin, Benjamin; Wang, SuYin Grass; Chen, Yu‐Sheng; Betley, Theodore A.
Abstract: The trichromium cluster ( tbs L)Cr3 (thf) ([ tbs L] 6− =[1, 3, 5‐C6 H9 (NC6 H4 ‐ o ‐NSi t BuMe2 )3 ] 6− ) exhibits steric‐ and solvation‐controlled reactivity with organic azides to form three distinct products: reaction of ( tbs L)Cr3 (thf) with benzyl azide forms a symmetrized bridging imido complex ( tbs L)Cr3 ( μ 3 ‐NBn); reaction with mesityl azide in benzene affords a terminally bound imido complex ( tbs L)Cr3 ( μ 1 ‐NMes); whereas the reaction with mesityl azide in THF leads to terminal N‐atom excision from the azide to yield the nitride complex ( tbs L)Cr3 ( μ 3 ‐N). The reactivity of this complex demonstrates the ability of the cluster‐templating ligand to produce a well‐defined polynuclear transition metal cluster that can access distinct single‐site and cooperative reactivity controlled by either substrate steric demands or reaction media.